Thermoreversible gelation polymer as an embolic material for aneurysm treatment: a delivery device for dermal fibroblasts and basic fibroblast growing factor into experimental aneurysms in rats. (25th September 2012) - Dobashi, Hisashi; Akasaki, Yasuharu; Yuki, Ichiro; Arai, Takao; Ohashi, Hiroki; Murayama, Yuichi; Takao, Hiroyuki; Abe, Toshiaki
Abstract : Background: This study evaluates whether thermoreversible gelation polymer (TGP) can be used as a delivery device to deploy dermal fibroblasts and cytokines into experimental aneurysms in rats. Methods: The right common iliac artery of rats was surgically ligated and an experimental aneurysm was created by applying exogenous elastase. Seven days later, two aneurysms were harvested and used as controls (Group A), two were embolized with pure TGP (Group B), two were embolized with TGP and basic fibroblast growth factor (bFGF) (Group C) and two were embolized with TGP loaded with rat dermal fibroblasts (Group D). The aneurysms were also embolized with TGP mixed with dermal fibroblasts and bFGF at different concentrations (10 ng/ml: Group E (n=2), 100 ng/ml: Group F (n=2), 1000 ng/ml: Group G (n=2)). Each aneurysm sample was harvested after 7 days and histologic analyses were performed. Results: The most advanced thrombus organization in the aneurysm, such as prominent fibroblast proliferation and collagen deposition, was observed in Groups E, F and G, although there was no noticeable difference between the groups. Moderate thrombus organization was seen in Group D and minimal thrombus organization was seen in Groups B and C. Conclusions: TGP mixed with both dermal fibroblasts and bFGF induced the most advanced thrombus organization in the experimental aneurysms followed by TGP mixed only with dermal fibroblasts. TGP may be useful as a delivery device to deploy fibroblasts and cytokines into aneurysms.